2002
DOI: 10.1023/a:1016536725958
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-Inducible Expression of SPARC/ Osteonectin/ BM40 in MDA-MB-231 Human Breast Cancer Cells Results in Growth Inhibition

Abstract: SPARC (secreted protein acidic and rich in cysteine)/BM40/Osteonectin is a matricellular protein with multiple effects on cell behaviour. In vitro, its major known functions are anti-adhesive and anti-proliferative, and it is associated with tissue remodelling and cancer in vivo. SPARC is overexpressed in many cancers, including breast cancer, and the effects of SPARC seem to be cell type-specific. To study the effects of SPARC on breast cancer, we transfected SPARC into the MDA-MB-231 BAG, human breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 38 publications
8
53
2
2
Order By: Relevance
“…Two recent in vitro studies delineate the potential of SPARC as a suppressor of tumorigenic potential in human melanoma and breast cancer cells via the addition of either antisense RNA or the transfection of SPARC (Ledda et al, 1997;Dhanesuan et al, 2002). Finally, our study demonstrates that the further investigation of SPARC is warranted due to its status as a potential prognostic and therapeutic agent.…”
Section: Discussionmentioning
confidence: 67%
“…Two recent in vitro studies delineate the potential of SPARC as a suppressor of tumorigenic potential in human melanoma and breast cancer cells via the addition of either antisense RNA or the transfection of SPARC (Ledda et al, 1997;Dhanesuan et al, 2002). Finally, our study demonstrates that the further investigation of SPARC is warranted due to its status as a potential prognostic and therapeutic agent.…”
Section: Discussionmentioning
confidence: 67%
“…26 Other investigators showed that forced expression of SPARC inhibited growth of human ovarian cancer cells in immunodeficient mice and in breast cancer cells in vitro. 27 SPARC-null mice exhibited increased proliferation of mesangial cells, 28 as well as, increased insulin growth factor signaling. 29 The protein also suppressed the growth of pancreatic cancer cells and glioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the tumour growth of glioma cells overexpressing SPARC was delayed in vivo (Schultz et al, 2002). An inhibitory effect of SPARC on proliferation and migration has been found in breast and ovarian carcinoma cells (Dhanesuan et al, 2002). Infection of MDA-231 breast carcinoma cells with osteonectin decreased the in vitro invasion of these cells through Matrigel (Koblinski et al, 2005).…”
Section: Discussionmentioning
confidence: 98%